2019
DOI: 10.11604/pamj.2019.33.100.17094
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hypertension among diabetic patients in Public Hospitals of the Central Zone, Tigray, Ethiopia 2018: unmatched case-control study

Abstract: Introduction Hypertension, among diabetic patients, is a worldwide public-health challenge and a leading modifiable risk factor for other cardiovascular diseases. The main purpose of this study was to identify determinants of hypertension among diabetic patients. Methods Data were collected from January to March 2018 using an interviewer-administered structured questionnaire. Data collectors and supervisors were trained before the period of data collection. The question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 40 publications
6
37
3
Order By: Relevance
“…Different studies showed that an increase in the duration of T2 DM is associated with an increased prevalence of hypertension. 20,28,37,38 On the contrary, the prevalence of HTN in this study is lower than the findings reported in Jordan (72.4%) 38 and Iraq (89.6%). 20 The higher prevalence in these studies is most likely due to the cut point used for the diagnosis of hypertension, which was defined at a lower level of blood pressure (>130/80 mmHg).…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Different studies showed that an increase in the duration of T2 DM is associated with an increased prevalence of hypertension. 20,28,37,38 On the contrary, the prevalence of HTN in this study is lower than the findings reported in Jordan (72.4%) 38 and Iraq (89.6%). 20 The higher prevalence in these studies is most likely due to the cut point used for the diagnosis of hypertension, which was defined at a lower level of blood pressure (>130/80 mmHg).…”
Section: Discussioncontrasting
confidence: 68%
“…So the higher BMI in Jordan might be the possible cause for the higher prevalence of hypertension because high BMI is associated with increased risk of hypertension. 20,28,[38][39][40][41][42] The higher prevalence of hypertension reported in three Moroccan regions (70.4%) 29 is perhaps related to the fact that most diabetics were aged 60 years old and over, having a high risk of hypertension. 29,43,44 The odds of getting HTN among T2DM patients was higher in the age group of 50-59 years than the age group of <50 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations